2020
DOI: 10.1111/psyg.12558
|View full text |Cite
|
Sign up to set email alerts
|

Use of day services improved cognitive function in patients with Alzheimer's disease

Abstract: Aim: Day services (DS) are part of the public nursing care system in Japan. The purpose of DS is to help elderly individuals maintain mental and physical functions, eliminate feelings of isolation among homebound users, and reduce the burden of care on family members. However, the relationship between DS and the progression of Alzheimer's disease (AD) remains unclear. Methods: We retrospectively analyzed 161 AD patients based on available Mini-Mental State Examination (MMSE) scores. The patients were divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…As apathy is a major symptom of AD, people with AD are generally reluctant to attend DS centres. In our previous study, approximately one‐third of patients with AD chose not to participate in DS 13 . We also observed this tendency in the present study, where DS users were mostly older women with moderate to severe dementia.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As apathy is a major symptom of AD, people with AD are generally reluctant to attend DS centres. In our previous study, approximately one‐third of patients with AD chose not to participate in DS 13 . We also observed this tendency in the present study, where DS users were mostly older women with moderate to severe dementia.…”
Section: Discussionsupporting
confidence: 81%
“…This study found more frequent DS use per week was significantly positively related to HDS-R score changes, whereas our previous study found no such significant relationship with MMSE score changes. 13 Because this discrepancy might be related to the difference in items on these cognitive instruments, we examined specifically which HDS-R items showed improvement. Serial 7 scores showed significant improvement among DS users.…”
Section: Discussionmentioning
confidence: 99%
“…12 Recently, the HDS-R and MMSE have also been used for regular cognitive assessment of AD patients. 15,16 For the family assessments of AD stage, we used the Functional Assessment Staging (FAST) scale, 17 which classifies AD progression into seven stages. We then compared the discrepancy between FAST-based family-assessed AD stage and diagnosed AD stage.…”
Section: Introductionmentioning
confidence: 99%
“…Both are commonly used screening assessments in Japan, although the HDS‐R was found to be superior to the MMSE as a screening instrument for AD in a previous study 12 . Recently, the HDS‐R and MMSE have also been used for regular cognitive assessment of AD patients 15,16 . For the family assessments of AD stage, we used the Functional Assessment Staging (FAST) scale, 17 which classifies AD progression into seven stages.…”
Section: Introductionmentioning
confidence: 99%
“…Of relevance, Suspected Non-Alzheimer's Disease Pathophysiology is seen in 17% to 35% of patients with mild cognitive impairment, and 7% to 39% of patients with clinically probable AD do not exhibit beta amyloid pathology [38]. Recently suppressed AD progression has been reported by appropriate pharmacological management [39] as well as non-pharmacological management by social care use such as daycare [40] in Japan. Memory clinic settings and a high proportion of daycare use would cause suppressed AD progression in this study population.…”
Section: Strengths and Limitationsmentioning
confidence: 99%